Uncommon Presentation of a Benign Nasopharyngeal Mass in an Adolescent: Comprehensive Review of Pediatric Nasopharyngeal Masses - Victor M. Duarte; Yuan F. Liu; Nina L. Shapiro (Case Reports in Pediatrics)
Nasopharyngeal masses in the pediatric population are quite rare, and the majority of these are benign. In adolescent boys, there should be a high index of suspicion for juvenile nasopharyngeal angiofibromas. When malignant, the most common lesions encountered are rhabdomyosarcomas, carcinomas, and lymphomas. We report a single case from a tertiary care institution of an adolescent male with an unusual presentation of a benign nasopharyngeal mass and provide a comprehensive review of pediatric nasopharyngeal masses. Whenever possible, radiographic imaging should be obtained, in addition to biopsy, to assist in the diagnosis of pediatric nasopharyngeal masses.